2019
DOI: 10.6007/ijarbss/v9-i9/6392
|View full text |Cite
|
Sign up to set email alerts
|

Role of Work Motivation as Moderator between Breach of Psychological Contract and Workplace Deviant Behavior among Employees

Abstract: The present study examined the effect of psychological contract breach on workplace deviant behavior with the help of social exchange theory. Furthermore, the current study also investigated the buffering effect of work motivation between the relationship of psychological contract breach and workplace deviant behavior. The current study was quantitative and cross-sectional survey was designed to collect data. Data was gathered using structured questionnaire. Stratified sampling method used to select sample and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The higher the perceived work motivation, the lower the workplace deviant behavior. This research supports the study conducted by Malik et al (2019) which states that work motivation has a negative and significant effect on workplace deviant behavior. If employees are intrinsically and extrinsically motivated, they will not cause negative and dangerous behavior and have friendly relationships with all colleagues.…”
Section: The Effect Of Work Motivation On Workplace Deviant Behaviorsupporting
confidence: 90%
See 1 more Smart Citation
“…The higher the perceived work motivation, the lower the workplace deviant behavior. This research supports the study conducted by Malik et al (2019) which states that work motivation has a negative and significant effect on workplace deviant behavior. If employees are intrinsically and extrinsically motivated, they will not cause negative and dangerous behavior and have friendly relationships with all colleagues.…”
Section: The Effect Of Work Motivation On Workplace Deviant Behaviorsupporting
confidence: 90%
“…Love for incentives can lead to workplace deviant behavior, such as a lack of effort to channel work and not contribute to organizational goals but increase profits. Malik et al (2019) found a positive and significant relationship between psychological promise violations and workplace deviant behavior. Work motivation has a significant relationship between psychological contract violations and workplace deviant behavior.…”
Section: Introductionmentioning
confidence: 87%
“…Recent literature has shown a prevalent presence of deviant work behaviours in Asian countries (Malik, Bakri, Ajmal, & Malik, 2019b;Qureshi & Hassan, 2019;Sarwar, Naseer, et al, 2019). Furthermore, nurses face family pressure, and nursing is a stressful profession in Asia, especially in Pakistan because of long duty hours and high physical demands (Sarwar, Bashir, & Karim Khan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Haldorai et al (2020) demonstrated that all employees have the propensity to engage in this damaging behaviour at the workplace. Malik et al (2019), Robinson et al (2019), and Shoaib and Baruch (2019) confirmed that work-related deviant behaviour is more rampant among the support personnel since it is assumed that the lower-level workers are more prone to participating in misconduct because they have more time to take revenge on those who have mistreated them. While administrators in the majority of organisations have demonstrated an inadequate intention of implementing research findings on deviant behaviour because they view it as counterproductive, Qu et al (2020) suggested that relatively insignificant deviant behaviours by the support staff may lead to the high-profile controversies such as those occasionally featured in the news.…”
Section: Work Deviant Behaviourmentioning
confidence: 80%